2012
DOI: 10.1063/1.4726118
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation of co-evaporated ZnPc:C60 blend film for highly efficient organic photovoltaics

Abstract: We demonstrate phase separation of co-evaporated zinc phthalocyanine (ZnPc) and fullerene (C60) for efficient organic photovoltaic cells. With introducing a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) film and a crystalline copper iodide film on indium tin oxide, 20-nm-thick ZnPc film adopts a lying-down crystalline geometry with grain sizes of about 50 nm. This surface distributed with strong interaction areas and weak interaction areas enables the selective growth of ZnPc and C60 molecules durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 34 publications
0
44
1
Order By: Relevance
“…Copper halides are p-type wide-bandgap semiconductors, thin films of which can be prepared by vacuum-or solution-based processes. Because of their compatible energy levels and strong interaction with organic molecules, our previous works have showed that copper halides can act as hole transport layers or structural templates for improving organic photovoltaics [35,36]. Here, we demonstrate the manipulation of halide crystallites in CNT networks at nanoscale by utilizing a pulse photonic curing system.…”
Section: Introductionmentioning
confidence: 92%
“…Copper halides are p-type wide-bandgap semiconductors, thin films of which can be prepared by vacuum-or solution-based processes. Because of their compatible energy levels and strong interaction with organic molecules, our previous works have showed that copper halides can act as hole transport layers or structural templates for improving organic photovoltaics [35,36]. Here, we demonstrate the manipulation of halide crystallites in CNT networks at nanoscale by utilizing a pulse photonic curing system.…”
Section: Introductionmentioning
confidence: 92%
“…All of the C 60 films that were treated with solvent spin-coating or SVA exhibited an increase in absorption intensity between 300 to 500 nm compared to the untreated films. This absorption increase was caused by light scattering from the nanocrystals [32,33], and increase crystallinity of nanocrystallized C 60 films [34]. The UV-Vis absorption of the film subjected to SVA with n-C 6 H 14 changed significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, defocused TEM has been shown to provide questionable results [12]. EFTEM creates a superior contrast and has been confirmed to work on P3HT:PCBM systems [3,17] as well as many other materials systems [19,20]. Combining EFTEM with the FIB cross section preparation technique, cross sections made from functioning devices give us the ability to see phase separation and charge collection pathways in actual devices.…”
Section: Eftem Imagesmentioning
confidence: 92%